Pengaruh Green Accounting Dan Kinerja Lingkungan Terhadap Kinerja Keuangan Perusahaan Sub Sektor Tambang Batubara - Maharani, Defa Putri; Palupi, Dyah; Dassaad, Dassaad; Wahyudi , Budi; Riyanti, Riyanti (Politeknik Negeri Ambon, 2024)
This research aims to determine and analyze the influence of Green Accounting on financial performance, the influence of environmental performance on financial performance, and the influence of Green Accounting and environmental performance on financial performance in coal mining subsector companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. This research uses 35 samples of coal mining subsector companies listed on the Indonesia Stock Exchange (BEI). The sampling technique uses the purposive sampling method. Purposive sampling is a sampling method taken based on criteria determined by the researcher. The variable in this research is financial performance which uses profitability ratios as measured by ROA and ROE as dependent variables and Green Accounting and Environmental Performance as independent variables. This research uses multiple linear analysis methods and uses SPSS version 25 software as a tool for testing multiple linear regression and descriptive statistical tests. The results of this research show that Green Accounting and financial performance calculated using ROA have an influence while using ROE calculations have no effect. Environmental performance does not have a significant effect on financial performance calculated using ROA, while that calculated using ROE has a significant effect. Green Accounting and environmental performance on financial performance simultaneously independent variables have an influence on the dependent variable. Keywords: Green Accounting, Environmental Performance, Financial Performance (ROA) and (ROE)